1905 Ind. Acts 688 - (:unkn) unknown (My University, 1905)
Weapon- Furnishing to Minor, § 450: Prohibited selling, bartering, exchanging, disposing of, or furnishing any dirk, Bowie-knife, slung-shot, metal knuckles, pistol cartridges, or other deadly weapon which can be carried concealed, to anyone under the age of twenty-one. Violators guilty of a misdemeanor, fined not less than five nor more than fifty dollars.
Keywords: TRANSFER - MINORS